Local emergency management and comprehensive emergency management (CEM): A discussion prompted by interviews with Chief Resilience Officers. (September 2022) - Jensen, Jessica; Kirkpatrick, Sarah
Abstract: Since the 1970s, emergency management agencies, associations, and standards have declared the emerging profession to be responsible for facilitating the framework within which preparedness, response, mitigation, and recovery are undertaken for all hazards. Still, many claim local level emergency management personnel may not be involved in all of these areas, at least not much, and, certainly, not equally. Meanwhile, disasters continue to increase in number and negative consequences. Against this backdrop, a new position, Chief Resilience Officer, has emerged within local government in the United States. This manuscript presents data from Chief Resilience Officers regarding what they do and what they perceive local emergency management personnel to do. Most individuals in these roles facilitate the framework in which their communities address community disaster root causes, vulnerability, mitigation, and/or recovery as part of their role. And most perceive local emergency management personnel to be dedicated to preparedness and response alone. These findings are discussed in the context of what the field claims as its purview at the national level and opportunity for local level emergency management practice in the future.